(untitled) (Research, Society and Development, 2020)
In view the intense use of natural resources, environmental education has an important role in promoting changes in the way society views environmental issues. In this context, the university has a decisive role in promoting actions, which bring to society knowledge about these resources and the need for their sustainable use, linked to personal and collective interests. This work aimed to report the experience of three editions of the event “Plant this Idea”, allusive to Arbor Day, in which seedlings of native forest and fruit species were donated, distribution of educational booklets to the community, and visits to a spring recovered in an area of ​​permanent urban preservation. Throughout the editions, the event held in different strategic points of the city, resulted in the donation of 3,500 seedlings, collected with the support of partners. The action culminated in the exchange of experiences between Petians and the community, contributing to the personal and professional development of academics, while also promoting the visibility of the university, the Forest Engineering course and the Tutorial Education Program - Forest Engineering (PET-EF).